Speaking for Understanding: Rules for Teachers - Johnson, Adrian (Journal of Modern Languages, 2017)
This article considers words of praise (or teachers who cared about their subjects and their pupils). The key issue here is clearly the gap that exists in some classrooms between what we are aiming at in education, and what we are in some cases, at least, actually achieving. The article mentions that, there are many reasons for this gap: some teachers have been given inadequate training, some lack a real interest in their job; some find the pressures on them too great; and so on.